The effects of back and front squat exercises on sprint speed and vertical jump: a pilot study - Balderree, A. S.; DeBeliso, M. (International Journal of Sports Science, 2019)
Performing back squats (BSQ) has been one of the most common and popular types of resistance training (RT) modalities to increase muscular strength and power output for the purpose of improving athletic performance. Front squats (FSQ), while not as popular as the BSQ, are arguably another squat modality that may improve athletic performance.